2010
DOI: 10.2108/zsj.27.629
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Chemotactic Response to Sodium Acetate in the NematodeCaenorhabditis elegans

Abstract: In this study, we investigated the chemotactic response of a wild-type (N2) nematode (Caenorhabditis elegans) to a water-soluble attractant, sodium acetate, after pre-exposure to the chemical. The chemotactic response to 1.0 M sodium acetate of the non-exposed control nematodes was lower than that of the nematodes that were pre-exposed to 1.0 M sodium acetate for 90 min (p < 0.05). The increase in the response to sodium acetate was observed up to 6 hr, but not at 12 hr after exposure. To clarify the mechanism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…13,17,23,25,32) bas-1(tm351) and bas-1(ad446) mutants are defective in an aromatic amino acid decarboxylase required for serotonin and dopamine production. 33) The chemotaxis index for NaCl of nicotine−/NaCl+ bas-1 mutants was significantly lower than that of nicotine−/NaCl− mutants (p < 0.01).…”
Section: Necessity Of Dopamine Signaling In Augmentation Of Gustatorymentioning
confidence: 99%
See 1 more Smart Citation
“…13,17,23,25,32) bas-1(tm351) and bas-1(ad446) mutants are defective in an aromatic amino acid decarboxylase required for serotonin and dopamine production. 33) The chemotaxis index for NaCl of nicotine−/NaCl+ bas-1 mutants was significantly lower than that of nicotine−/NaCl− mutants (p < 0.01).…”
Section: Necessity Of Dopamine Signaling In Augmentation Of Gustatorymentioning
confidence: 99%
“…24,25) Last larval (L4) stage nematodes have a crescent structure around the vulva; this structure disappears in the YA stage and thus was absent in all experimental animals. To obtain synchronous hermaphrodites, 50 gravid nematodes were transferred to fresh NGM plates with or without 0.3 mM nicotine and incubated for 3 h at 25°C to lay eggs.…”
Section: Introductionmentioning
confidence: 99%
“…In C. elegans , continuous presentation of chemical and mechanical stimuli can cause a decrease in the level of response to the same stimuli [7], [25][27]. Recently, Matsuura et al [28] showed that the chemotactic behavior of C. elegans to Sodium Acetate was significantly enhanced when the animals were pre-exposed to the chemical for 90 minutes. This increase was observed for about 6 hours after pre-exposure but not after 12 hours.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, lead acetate, a soluble lead compound, was used for CE to uptake lead. CE displays short term (<12 h) chemotactic responses to acetate (Matsuura et al 2010). Acetate is used by the nematodes for fatty acids biosynthesis (Rothstein 1972).…”
Section: Methodsmentioning
confidence: 99%